Corporate social responsibility in the Mexican oil industry: Social impact assessment as a tool for local development - Armando García-Chiang (International Journal of Corporate Social Responsibility (JCSR), 2018)
Mexico's 2008 energy reform established that Petróleos Mexicanos and its subsidiary entities could contract with individuals or corporate entities for labor and the provision of required services to improve the implementation of its activities. The reform has allowed private companies to become more involved in the process of oil extraction and to implement Integrated Petroleum Exploitation Contracts. This participation of the private sector has brought with it the need to evaluate its activities' social and environmental impact on the territory. One of these evaluations' main objectives is to project Corporate Social Responsibility schemes. We can see from experience that it is possible for private oil companies' participation in CSR schemes to contribute to local development, but the application of CSR actions does not in itself imply an impact on local development. This article aims to show the case of a pioneering experience in Mexico concerning the link between academics and the segment of oil companies that try to assess their activities' social impact and implement Corporate Social Responsibility schemes under federal regulations. In order to achieve it, a work team belonging to Universidad Autónoma Metropolitana has developed a methodology that uses quantitative and qualitative data. The main results of this case study show us that it is necessary to develop appropriate approximation and assessment methodologies for implementing Corporate Social Responsibility actions in each territory in order to stimulate local development. Moreover, there are two essential conditions for actually achieving results for local development by investing in communities within the context of CSR actions in oil-production regions. The first of these conditions is a "territorialization" of the proposals, and the second is the creation of different types of CSR actions. These last two conclusions are also challenges that Mexico's fledgling private oil sector will have to solve in the very near future with the objective of improving its relations within the social and environmental context where it carries out its activities.
Keywords: 650; CSR; Social impact Assesment; Territorialization; Local development; Mexico; Oil industry